UPAYA MENINGKATKAN KOMPENTESI CALON GURU (PRAKTIKAN) MELALUI SKENARIO PPL PEMBELAJARAN KIMIA DI SEKOLAH MITRA PPL - Gulmah Sugiharti (Jurnal Pendidikan Kimia (JPKim), 2014)
Abstract This article report from an action research,  aims to Strengthening Classroom Management,  question skills and reinforcement learning Competencies through  PPL-scenes (site experience) on  teaching chemistry. This research conduct  in SMA Negeri 1 Tanjung Pura Langkat  Province of North Sumatera by student training school (which take) PPL  activities .  The action research data collect by applying the technique of observation and interpretation simultaneously. The focus of this study is the observation in classroom management competence, questioning skills, giving reinforcement by student PPL Chemistry, in the learning process cycle unit Chemistry. The format of observations taken from 2012 UPPL Referring as an instrument and descriptive method used to data analysis. The research data shows  (1). To understand and recognize the mistake in learning activities Chemistry student behavior during the learning process, the student has increased sensitivity, especially at the end of the first cycle. (2). There are efforts through trial and error on the situation facing the class, after the experimentalist began to recognize the use of techniques of classroom management, the provision of reinforcement and questioning skills. (3). Student have been able to use classroom  management, giving  reinforcement and questioning skills in a more professional and situational aspects into account at the end of the third cycle. (4). Action research cycles have been successfully established practitioner competence in the use of classroom management, asking and giving reinforcement to the situation facing the class. Based on the analysis above action research proved very suitable to form an calu student competence as a Chemistry teacher. Keywords :  action research; teacher competencies; teaching chemistry; school  partner PPL